Model inspections in the engineering of collaborative cyber‐physical systems with instance‐level review diagrams. Issue 5 (17th October 2021) - Daun, Marian; Brings, Jennifer; Weyer, Thorsten
Abstract: Model inspections are important to ensure high‐quality software and to satisfy legal obligations in model‐based engineering processes. As model‐based specifications are typically documented on type‐level, errors concerning the interactions between multiple system instances can go unnoticed. For collaborative cyber‐physical systems (CPS), a plethora of possible instance‐level configurations need to be taken into account. Therefore, we propose the definition of instance‐level review diagrams that show representative interactions of instance‐level configurations that help detect defects in the system specification. To evaluate the approach, we conducted a controlled experiment whose results indicate that instance‐level review diagrams have—compared with type‐level diagrams—important positive effects on reviewing processes for behavioral specifications of CPS. Specifically, the experiment provides empirical evidence that instance‐level review diagrams are significantly more expressive and effective than type‐level diagrams. Abstract : This paper contributes a definition of instance‐level review diagrams in message sequence charts notation and reports results of a controlled experiment to evaluate instance‐level review diagrams. Results show that instance‐level review models support the validation of behavior specifications of collaborative cyber‐physical systems that operate in changing system network configurations.